Efficiency of Ankaferd Blood Stopper Used in Bleeding Control on Intraabdominal Adhesions Formed Postoperatively. (July 2014) - Behçet, AL; Kılıç, Hasan; Zengin, Suat; Güler, Mehmet; Taysi, Seyithan; Yıldırım, Cuma; Sarı, İbrahim
Purpose: The purpose of this study is to investigate the hispathological, biochemical, and clinical efficiency of Ankaferd Blood Stopper (ABS) in preventing postoperative intraabdominal adhesions. Method: A total of 40 Wistar albino species female rats were randomly separated into 4 groups. For the control group, 1 mL normal saline was administered; and for the second, third, and fourth groups 0.5, 1, and 2 mL, respectively, ABS was administered. Statistical analyses were evaluated with Tukey and analysis of variance test. Findings: Significant increase was observed in fibroblast and vascularization microscopically with increasing amount of ABS used. Degree of adhesion in the group administered with normal saline was lower compared to the other groups. Adhesion thickness and prevalence macroscopically increased with the increasing amount of ABS used in groups. Conclusion: It was determined in our study that ABS is not efficient in preventing intraabdominal adhesions; on the contrary, adhesions were increased with the increased amount of ABS used.